Relation of serum 25(OH) D with variables of thyroid and lipid profile in perimenopausal women - Rani, Poonam; Gupta, Seema; Gupta, Gaurav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Deficiency of vitamin D is quite prevalent among elderly population or postmenopausal women worldwide and may affect various function of the body. The status of its deficiency with their relation with other variables are not well explored in perimenopausal women. Methods: 100 perimenopausal women from the department of obstetrics and gynaecology were selected without having known risk of thyroid disorder and cardiovascular disease. The age group criteria for these women were 40 to 50 years. Thyroid profile including TSH, T3, and T4 were estimated by using enzyme linked immunesorbent assay. Serum levels of 25(OH) D3 was estimated by using spectrophotometric method. Lipid profile including TC, TG and HDL-C were estimated CHOD-POD method, GPO-PAP method, and CHOD-POD/Phosphotungustate method. LDL-C was calculated by friedewald formula. Results: There 58 women were presented with insufficient amount of vitamin D. They were characterised with increased BMI, elevated thyrotropin alongwith lower concentrations of T3 and T4. Increased levels of TC, TG and LDL-cholesterol alongwith lower concentration of HDL-C were also observed in women with vitamin d deficiency. Women having vitamin D deficiency were presented with overweight (OR-18.0, p-value=<0.001) and dyslipidemia (OR-12.13, p-value≤0.001). Vitamin D was negatively correlated with variable i.e. BMI, TSH, TC, TG and LDL-C. This negative association was significant (<0.001) while HDL-C and T4 were positively correlated with vitamin D levels in this study population. Conclusions: Vitamin D deficiency frequently occurs in middle aged perimenopausal women. Negative correlation of it with BMI, TSH and lipid variables may suggest the development of cardiovascular disease and hypothyroidism in coming years. Vitamin D supplements or vitamin D containing diet and regular exposure to sun is highly recommended to perimenopausal women.